Innovations in Water Management for Sustainable Development of Higher Education Institutions: Experience from Ton Duc Thang University, Vietnam - Huu Nguyen, Cuong; Nguyet Thi Tran, Suong; Anh Duc Nguyen, Nghi (Journal of Sustainability Perspectives, 2021)
Ton Duc Thang University (TDTU), which was established in 1997, is a fully autonomous public university in Vietnam. After over 22 years of development, TDTU is now the number one university in Vietnam for all aspects. In 2019, TDTU was ranked the 1st in Vietnam and ranked 165th in the world on sustainable development by UI GreenMetric World University Rankings (UI GreenMetric). Among six categories of UI GreenMetric, including: setting and infrastructure, energy and climate change, waste, water, transport, and education, the water category of TDTU achieved 725 points out of 1000 maximum points (72.50%). This paper presents water management of TDTU, focusing on water conservation, water recycling, the use of water efficient appliances and piped water consumption. Specifically, the paper highlights innovations in water management that TDTU has implemented during the past few years. The paper concludes that sustainable water management makes great contribution to sustainable development of a higher education institution